Diverse Colletotrichum species cause anthracnose of tea plants (Camellia sinensis (L.) O. Kuntze) in China - Wang, Yu-Chun (Sci Rep, 2016)
Anthracnose caused by Colletotrichum is one of the most severe diseases that can afflict Camellia sinensis. However, research on the diversity and geographical distribution of Colletotrichum in China remain limited. In this study, 106 Colletotrichum isolates were collected from diseased leaves of Ca. sinensis cultivated in the 15 main tea production provinces in China. Multi-locus phylogenetic analysis coupled with morphological identification showed that the collected isolates belonged to 11 species, including 6 known species (C. camelliae, C. cliviae, C. fioriniae, C. fructicola, C. karstii, and C. siamense), 3 new record species (C. aenigma, C. endophytica, and C. truncatum), 1 novel species (C. wuxiense), and 1 indistinguishable strain, herein described as Colletotrichum sp. Of these species, C. camelliae and C. fructicola were the dominant species causing anthracnose in Ca. sinensis. In addition, our study provided further evidence that phylogenetic analysis using a combination of ApMat and GS sequences can be used to effectively resolve the taxonomic relationships within the C. gloeosporioides species complex. Finally, pathogenicity tests suggested that C. camelliae, C. aenigma, and C. endophytica are more invasive than other species after the inoculation of the leaves of Ca. sinensis.